Innovative Approaches in Social Work Education: Exploring Strategies to Enhance Learning and Practice Preparation - Bhavya. P; M.P Somashekar (International Journal of Contemporary Sciences (IJCS), 2024)
This paper explores innovative approaches to teaching in social work education aimed at enhancing both learning outcomes and practice preparation. Drawing upon a review of current literature and best practices in pedagogy, this study examines various strategies that have been implemented to enrich the educational experience for social work students. The article begins by outlining the challenges faced in traditional social work education models and underscores the need for creative teaching methodologies to better equip students for the complexities of contemporary social work practice. It then delves into several innovative approaches, including experiential learning techniques, technology integration, interdisciplinary collaboration, and community engagement initiatives. Each approach is examined in terms of its potential benefits and challenges, as well as its applicability to different learning environments and student populations